Thermogravimetric Method for Accurate Determination of Thermodynamic Quantities at High Temperatures - Harbbi, K. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This researd exhibit’s a method to determine the change in Gibbs function,(enthai py,entropy. and specific heat capacity) tor monovariant heterogeneous equilibria .The thermodynamical quan.tities were obtained jndirectly with m the measurment of temperature dependent on eql,lilibrium system.